2019
DOI: 10.1080/07352166.2019.1569468
|View full text |Cite
|
Sign up to set email alerts
|

The contradictions of participatory planning: Reflections on the role of politics in urban development in Niterói, Brazil

Abstract: Despite the broad celebration of Brazil's urban reform movement, recent events in Brazil have called attention to a paradox focused on the disappointing results of this movement to deal with Brazil's complex urban context. Taking this "impasse" as a starting point, this article focuses on the role of politics and its relationship to economic interests in urban development in which much decision making around urban policy takes place to understand why Brazil's progressive legislation has not succeeded in creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…Our research shows capacity of a given urban form for adaptation and confirms that social organization can have a dramatic impact on the inner-patterns of public spaces. In line with previous studies (Koch and Latham, 2011;Yusof and Kozlowski, 2018;Friendly, 2019), we recognized that diverse people's voices and bodies -of a different ethnic identity and gender-are encountered and recognized, affect the ways people can consume and shape the public spaces. In Whitechapel market, each gender has its own key activity points in the market and using isovist technique we showed that these points differ in strength and weakness, influenced by location, vistas, number of users, and functioning.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our research shows capacity of a given urban form for adaptation and confirms that social organization can have a dramatic impact on the inner-patterns of public spaces. In line with previous studies (Koch and Latham, 2011;Yusof and Kozlowski, 2018;Friendly, 2019), we recognized that diverse people's voices and bodies -of a different ethnic identity and gender-are encountered and recognized, affect the ways people can consume and shape the public spaces. In Whitechapel market, each gender has its own key activity points in the market and using isovist technique we showed that these points differ in strength and weakness, influenced by location, vistas, number of users, and functioning.…”
Section: Discussionsupporting
confidence: 86%
“…In line with de Lucio's statement (2000) that any definition of public spaces should include "a vision of public spaces as psychical places where people can participate in public life and where people's claims can be voiced", Ortiz et al (2004) defined public spaces as "places of interrelation, social encounter and exchange, where individuals and groups with various interests converge". It is now common to assume that in addition to class and income, ethnic identity and gender are the main factors that affect the way in which people can consume and shape the public spaces (McDowell, 1999;Yusof and Kozlowski, 2018;Friendly, 2019). Following globalization processes, the adaptation of the public space in the western inner-cities to the use of minority ethnic communities was empirically studied and theoretically investigated from various points of view.…”
Section: Introductionmentioning
confidence: 99%
“…De Vries, 2016; Freitas, 2017; Friendly and Stiphany, 2019). Though the proposal of participatory planning aims to promote social justice through urban reforms (Friendly, 2019; Rolnik, 2011), public participation actually turned to be the useful tool for the middle classes to protect their vested interests (Nogueira, 2020), which further reinforced rights of the rich and legitimised middle classes’ claims (Caldeira and Holston, 2015; Nogueira, 2020). This assertion develops the contemporary debates of socio-spatial segregation in the Global South, as those who live in the city have uneven capacities to get access to the state resources thus claims are unequally legitimised (Nogueira, 2020).…”
Section: Unravelling China’s Paradoxical Participatory Governancementioning
confidence: 99%
“…This assertion develops the contemporary debates of socio-spatial segregation in the Global South, as those who live in the city have uneven capacities to get access to the state resources thus claims are unequally legitimised (Nogueira, 2020). In this regard, studies regarding participatory planning in Brazil is contradictory and inconsistent, because social exclusion and spatial segregation still exist (Friendly and Stiphany, 2019; Friendly, 2019).…”
Section: Unravelling China’s Paradoxical Participatory Governancementioning
confidence: 99%
“…In this article, I view Brazil's urban transformations and debates on the right to the city through a focus on three issues: (1) the rights dimension of such debates; (2) the role of the social function of property in urban legislation; and (3) the role of insurgent planning evident in Brazil's urban social movements. This article is reflective and exploratory, based on a review of the literature, as well as the author's extensive work on cities in Brazil, urban policies, and the right to the city (Friendly, 2013(Friendly, , 2016(Friendly, , 2017(Friendly, , 2019Friendly and Stiphany, 2019). The next section traces the rights dimension of social citizenship.…”
mentioning
confidence: 99%